Coal seams in the South Moravia Lignite Coalfield - Josef Honěk; František Staněk; Kerstin Hoňková; Jan Jelínek (Acta Montanistica Slovaca, 2009)
In the most top sediments of the Vienna Basin in the south part of Moravia, two coal seams of low rank coal occur - the KyjovSeam and the Dubňany Seam. The area with these seams is called the South Moravian Lignite Coalfield (SMLC). The SMLC was chosenas suitable area for example digital modelling coal seams for purpose of evaluation the coal. In the contribution, development of bothseams in particular parts of the SMLC, chemical attributes, preparation, and utilization of coal are described. Phases and methodologyof deposit exploration in the SMLC, methods of sampling and overview of the laboratory results are described in detail.